Family Dinner at Frances Kamp Celebrating Cliff and Evie Macabee's 40th Anniversary - Watkins, Howard::::::::: (1988)
Cliff Macabee and Evie Macabee seated and hugging in front of Frances Kamp's golden Asian art work Fran's home at 6300 N. Palm Avenue #109, Fresno